Συσχέτιση της ποιότητας του νερού του ταμιευτήρα των Πολεμιδιών με την ευτροφική του κατάσταση μέσω της πολλαπλής γραμμικής ανάλυσης - Χατζηουρανίου, Γεωργία (Τμήμα Επιστήμης και Τεχνολογίας Περιβάλλοντος, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2018)
The water of Polemidia reservoir in Limassol, is exclusively used for irrigation of crops and it is enriched with water that has undergone tertiary treatment by the Sewerage Board of Limassol Amathus (SBLA). Until recently (2017), urban and industrial waste water from a nearby landfill, Vatι, entered the dam. The aim of this study is to correlate the water quality characteristics of the Polemidia reservoir with cyanobacteria blooming, the chemical oxygen demand (COD), dissolved oxygen, total coliforms, phytoplankton biovolume and chlorophyll - a for the period 2007-2015, through the multiple linear regression method. The results were obtained though the systematic environmental monitoring of the reservoir, which have been carried out by the Water Development Department based on the EU Water Framework Directive 2000/60/EC. Initially, the first summarizes the water quality characteristics of surface water and explains how the EU Framework Directive 2000/60/EC contributes to the monitoring of the Polemidia reservoir and to the recording of these parameters. The second chapter discusses the water quality characteristics that were used in the Matlab® platform in order to make correlation between blooming and water quality. Subsequently, the third chapter, presents the results of the environmental monitoring of the parameters recorded in the second chapter. In addition, the differences between the models and the collerations are provided. Through this diploma thesis, it was proven that the quality characteristics of the Polemidia reservoir water, which are modified by the inflows that end up in the dam, directly affect the eutrophic state of the reservoir and indicate mainly the phosphorus (P) as the regulator for the blooming of cyanobacteria. A significant reduction in the total phosphorus concentration of recycled water after 2010 changed the trends of all the above-mentioned parameters. Changes in phosphorus concentration also directly affected the genera of cyanobacteria that grow each time in the ecosystem. Chapter four summarizes the conclusions of the paper. At the end of the study, it is concluded that phosphorus (and not nitrogen) is the main nutrient that is acting as the limiting factor in the development of phytoplankton in Polemidia due to the large fluctuations in its concentration and its excessive reduction after 2010. The ratio showing the concentration of dissolved inorganic nitrogen in total phosphorus (DIN: TP), gives a better correlation of nutrients with the concentrations of the parameters studied. The DIN: TP ratio also includes the deposition of nitrogen, thus better presenting the availability of the elements in the Polemidia reservoir water. Finally, chapter five summarizes the future work.
Keywords: Reservoir; Polemidia; Crops; Water quality characteristics; Chemical oxygen demand; Phosphorus; Waste water; Πολεμίδια; Καλλιέργειες; Λύματα; Ποιοτικά χαρακτηριστικά νερού; Φώσφορο